Aesthetics of Artistic Discourse in the Novel "The Laz" by Tahar WattarAn Aesthetic Approach in the Narrative Perspective (مجلة إحالات, 2026)
The research is concerned with studying the narrative perspective in the novel “Al-Laz” by AlTaher Wattar. The mechanisms of manifestation of the narrative vision of the text are traced throughthe style and aesthetics of narrative discourse, depending on the characteristic diversity of discourses and the victory of a particular ideological vision. In this case, the method of intellectual and cognitive analysis was adopted for all the theoretical and ideological statements included in the text, accordingto the awareness of the fictional characters, who contributed greatly in crystallizing the aesthetics ofthe discourse, and according to the narrative perspective of the novel.